Preliminary evaluation of Neem (Azadirachta indica) extracts as altemative for cattle tick Boophilus microplus control - BENAVIDES-O., EFRAÍN; HERNÁNDEZ-M., GUSTAVO; ROMERO-N., ALVARO; CASTRO-A., HERNANDO; RODRÍGUEZ-B., JOSÉ LUIS (Revista Colombiana de Entomología, 2001)
Plant extracts are a probable alternative to reduce the dependence on pesticides to control ticks. Toe Neem tree (Azadiractha indica) is well known for its insecticidal properties. In a preliminary study, field and laboratory experiments were conducted to evaluate the use of Neem seed extracts as a control tool. Using the tick's Adult Immersion Test, the effect on the reproductive capability of ticks of aqueous, alcoholic, and ether solutions of seed extracts was evaluated. Toe possible toxicity of a 4% aqueous extract of seed was evaluated on rabbits through the test of ocular instillation, dermal sensitivity, intradermal inoculation, and entire immersion or dip. In the field, the effect of treating grazing cattle with a 5% hydrolase of Neem's seeds was compared agAinst the application of commercial acaricide (Arnitraz). through two consecutive tests with five and four animals per group. In the laboratory tests, The highest Percentage Control of the Reproductive Efficacy (PCONER) found corresponded to the ether solution at a 1:5 dilution (100%). The results on aqueous solutions suggested solubility or stability problems of the compound. Toe highest PCONER observed on the alcoholic extracts were of 70% and 69% respectively for dilutions 1:5 and 1:20. No rabbit showed an unfavorable reaction in the toxicity tests used. In the field tests, no difference was found in the tick counts between the two groups, neither in the first (t=0.50, .P>0.05) or in the second test (t=0.63, p>0.05), indicating that the seed hydrolase had a similar effect to the commercial acaricide. The definitive validation of this alternative will require field tests with a higher number of animals, stall tests, and evaluations using different types of formulations that could be practica! for their use under field conditions.